The superoxide dismutase (SOD) genes family mediates the response of Nilaparvata lugens to jinggangmycin and sugar - Sheraz, Ahmad; Zhu, Haowen; Dong, Qiaoqiao; Wang, Tingting; Zong, Suman; Wang, Huaiqi; Ge, Linquan; Wu, Tao (Frontiers in Physiology, 2023)
Objectives: Brown planthopper (BPH), Nilaparvata lugen Stål (Hemiptera: Delphacidae), is a major rice pest causing significant damage to rice throughout the world. Intensive pesticide usage often causes resistance in these seasonal pests, mainly through the modulation of antioxidant machinery. The superoxide dismutase (SOD) gene family is known for regulating BPH response to pesticides. Method: In the present study, we identified eight NlSOD genes from the NCBI using the BLASTP program. The bioinformatics analysis includes a phylogenetic tree, conserved domain, motifs, gene ontology (GO analysis), KEGG pathways, and protein-protein interaction, highlighting the distinctive functional elements of NlSOD genes. Additionally, the NlSOD genes showed expression in all developmental stages of BPH. Results: Under three sugars (glucose, sucrose, and trehalose) treatment, the respective upregulation of NlSOD8, NlSOD6, and NlSOD2 was noted. The NlSOD1 induced significantly under jinggamycin (JGM) deduced its potential as a key regulator of BPH response to the pesticide. Conclusion: Our study has provided detailed knowledge of the NlSOD gene family in-silico analysis and the defensive response to insecticide and sugar of BPH. We hope the results of this research will help to shed light on the resistance of BPH towards insecticide and sugar stress and help to control it more efficiently.